Normalisasi Kekerasan Perempuan Melalui Produk Jurnalistik (Analisis Wacana Kritis “ Sara Mills ” pada sindonews.com dan tribunnews.com) (Jurnal Ilmu Komunikasi dan Bisnis, 2023)
This research aims to analyze media discourse about journalistic products related to the normalization of violence experienced by women. and to reveal the subject-object position and reader position in journalistic products displayed by the media Sindonews.com and Tribunnews.com in the April 2022-January 2023 edition. This research uses critical discourse analysis methods from Sara Mills and uses Postmodern Feminism theory to analyze and reveal the meaning in texts about violence against women in the media. The approach used is qualitative using a critical paradigm. The results of the research show that presenting text to readers of Sindonews.com and Tribunnews.com Online Media objectifies women (victims) through sexist language so that it can be said to be a violation of the Journalistic Code of Ethics. This can be seen from the choice of words and writing of news headlines which represent a bad image for women. The author's recommendation through this research is that Media Sindonews.com and Tribunnews.com implement a study of the Journalistic Code of Ethics in conveying news and side with the interests of women so that women do not become victims a second time.